Relationship between electronic cigarette use, dual smoking habits, and psychological distress among youth in Northern Thailand: A cross-sectional study - Chakkraphan Phetphum; Atchara Prajongjeep; Kornkan Phuengnam (Tobacco Induced Diseases, 2024)
Introduction Amidst the escalating trend of electronic cigarette (e-cigarette) use and dual smoking habits among youth, understanding their potential impact on psychological well-being is imperative. Limited research has explored this relationship, particularly among youth in settings where e-cigarettes are banned. This study investigates the relationship between current e-cigarette and traditional cigarette use patterns and the presence of depression and anxiety symptoms among youth in Thailand.